Incompatible European partners? Cultural predispositions and household financial behavior - Michalis Haliassos; Thomas Jansson; Yigitcan Karabulut (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
The Eurozone fiscal crisis has created pressure for institutional harmonization, but skeptics argue that cultural predispositions can prevent convergence in behavior. Our paper derives a robust cultural classification of European countries and utilizes unique data on natives and immigrants. Classification based on genetic distance or on Hofstede's cultural dimensions fails to identify a single 'southern' culture but points to a 'northern' culture. Our findings support the relevance of cultural predispositions for financial behavior; and convergence of behavior over time in the face of common institutions, even for countries with great cultural distance from the country that created those institutions.
Keywords: Z1; G11; E21; 330; Household Portfolios; Household Finance; Culture and Institutions